The Religious Philosophy of Abdullah ibn Muhammad Al-Habashi Al-Harari and the Doctrines and Politics of Al-Ahbash: an Evaluation - Md. Thowhidul Islam (UNHI PRESS, 2021)
Shaikh Abdullah ibn Muhammad ibn Yusuf Al-Habashi Al-Harari of Ethiopia is a controversial Islamic scholar and founder of Al-Ahbash in Lebanon. He was involved in the struggle mainly with the Islamic fundamentalist Wahhabis there and was expelled from Ethiopia in 1947. After living in different cities, he settled down at Beirut, Lebanon in 1950. He was declared leader of the Jam’iyyat al-mashari’ al-khayriyya al-islamiyya (Association of Islamic Charitable Projects) in 1983 after the death of its founder Shiakh Muhiyy al-Din al-Ajuz. Since then, it has been known as ‘Al-Ahbash’ (the Ethiopians) after his title Al-Habashi. Al-Ahbash became one of the most controversial Muslim associations in the contemporary spectrum of Islamic groups because of its religious philosophy and doctrines. Al-Ahbash philosophy blended Sunni and Shi’a theology with Sufi spiritualism into a doctrinal eclecticism. Its ideological discourses mainly follow Shafi’i, Ash’ari and Maturidi doctrines. Al-Ahbash’s doctrine has also been influenced by some Sufi orders (tariqas) like Rifa’iyya and Qadiriyya. It emphasized Islam’s innate pluralism and determines the religious and political program, which do not fit with the conventional Islamists idea. It advocated for opposition to Islamic political activism and the use of violence against the ruling order. These attributes opposed to the political thoughts of many Islamic thinkers like Ibn Taymiyya, Ibn Abd Al-Wahhab, Sayyid Qutb. The most controversial issue in Al-Ahbash doctrine is the question of the relation among religion, politics, and the state in Islam. Al-Ahbash advocated the separation of religion and state and thereby rejected the idea of an Islamic state. Its views on education, women and science also contradict many of the above named writers opinions. Thus, Al-Ahbash represents a new but controversial view in Islam. This paper is aimed at understanding the philosophy and political doctrines of al-Ahbash.